2013
DOI: 10.1021/es303695f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticle Stabilization and Physicochemical Properties on Exposure Outcome: Acute Toxicity of Silver Nanoparticle Preparations in Zebrafish (Danio rerio)

Abstract: Nanotechnology has vast potential for expanded development and novel application in numerous sectors of society. With growing use and applications, substantial production volumes and associated environmental release can be anticipated. Exposure effect of nanoparticles (NP) on biological systems may be intrinsic to their physicochemical properties introducing unknown associated risk. Herein, we expand the knowledge of health and environmental impact of silver nanoparticles (AgNPs), testing the acute toxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 87 publications
3
35
0
Order By: Relevance
“…The values of IT, MI and PI indicators of plants grown on the solution of trisodium citrate did not differ significantly from the control values. In light of this, the obtained data allow to speculate that stabilized NPs acquire novel properties or functional qualities compared to non-stabilized ones, as has been reported previously (Cunningham et al 2013;Sharma et al 2014). It could mainly be connected with altered phase composition of tested solutions, rather than with the size of metal particles.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The values of IT, MI and PI indicators of plants grown on the solution of trisodium citrate did not differ significantly from the control values. In light of this, the obtained data allow to speculate that stabilized NPs acquire novel properties or functional qualities compared to non-stabilized ones, as has been reported previously (Cunningham et al 2013;Sharma et al 2014). It could mainly be connected with altered phase composition of tested solutions, rather than with the size of metal particles.…”
Section: Discussionsupporting
confidence: 69%
“…The resulting NPs adsorb negatively charged citrate ions on their surface and thus are stabilized due to electrostatic repulsion. The presence of stabilizing agents on the surface of NPs provides them new properties, which in turn predetermine the toxicity of nanomaterials (Cunningham et al 2013;Sharma et al 2014). So, search for ways to improve the physical and chemical properties of nanomaterials is still in progress, at the same time, careful control of nanoproducts for environment safety with the use of bioassays is also needed (Olkhovych et al 2016;Teplicky et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also point out that the transformation of nanosilver in environmental and biological media is strongly influenced by the concentration of S ion (S 2− and SH − ) and S-containing compounds, dissolved oxygen, Cl − , biological macromolecules (DNA and protein), other organic compounds that have strong affinity for either atomic or ionic silver, and lighting condition (6–8, 10, 33, 38, 52, 54, 6166). Among SO 4 2− , S 2− , Cl − , PO 4 3− , and EDTA, sulfide ligands are the most effective to reduce nanosilver toxicity by formation of Ag x S y (67).…”
Section: Behavior Of Nanosilver In Biological and Environmental Mediamentioning
confidence: 99%
“…However, the 2% solubility was measured at high concentrations of Ag 0 NPs (1000 mg/L and 144 mg/L respectively). Similarly, Ostermeyer et al, 5 measured 25 to 100% dissolution of 1 mg/L Ag 0 NPs in HEPES buffer and Cunningham et al 6 measured between 12% and 40% dissolution at 50 mg/L Ag 0 NPs in zebrafish embryo medium. Especially considering that at low concentration, the system is undersaturated with respect to Ag 2 O as observed by Liu et al 4 who found 100% dissolution for an initial Ag 0 NP concentration of up to 2 mg/L in DI water.…”
Section: ■ Physicochemical Argumentmentioning
confidence: 92%